ANALISIS PRESSURE BUILD-UP RESERVOIR GAS KONDENSAT DALAM FORMASI KARBONAT - Jodica Jodica; Onnie Ridaliani; Ghanima Yasmaniar (PETRO:Jurnal Ilmiah Teknik Perminyakan, 2019)
Different flow region will form in the reservoir when the gas condensate fluid flows with a bottom hole pressure below the dew point pressure. This flow region can be identified by the pressure build-up test analysis. This analysis can be done well on reservoir with homogeneous system and becomes more complex on reservoir with heterogeneous system. The purpose of this study is to find informations and characteristics about carbonate reservoir with gas condensate. Reservoir parameters that can be obtained are initial reservoir pressure (pi), permeability (k), skin factor (s), reservoir boundary (boundary), drainage area, and average reservoir pressure ( pr ). "JD-1" exploratory well penetrated the carbonate formation with the gas condensate hydrocarbon content. The well test analysis conducted is pressure analysis with pressure build-up testing and theanalysis results show a reservoir with a two-layer model, permeability value of 154 md, skin 13.8, initial pressure 3286.3 psia, and average reservoir pressure of 3285.7 psia.